2021
DOI: 10.1111/eje.12656
|View full text |Cite
|
Sign up to set email alerts
|

Assessing dentist and dental student knowledge of and attitudes towards shared decision‐making in the United Kingdom

Abstract: Introduction: Shared decision-making (SDM) is a partnership between healthcare professionals and patients when choosing care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 18 publications
(36 reference statements)
0
4
0
Order By: Relevance
“…Data are useful in describing current practices and estimating the influence of clinical training on practice patterns. The only empirical research on SDM practices in oral health settings have been conducted in Europe 19–29 . In the United Kingdom, two studies reported that roughly a quarter of practising dentists had experienced training in SDM 20,22 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Data are useful in describing current practices and estimating the influence of clinical training on practice patterns. The only empirical research on SDM practices in oral health settings have been conducted in Europe 19–29 . In the United Kingdom, two studies reported that roughly a quarter of practising dentists had experienced training in SDM 20,22 .…”
Section: Discussionmentioning
confidence: 99%
“…The only empirical research on SDM practices in oral health settings have been conducted in Europe. [19][20][21][22][23][24][25][26][27][28][29] In the United Kingdom, two studies reported that roughly a quarter of practising dentists had experienced training in SDM. 20,22 But there are no reports of the extent to which SDM is part of practice protocol.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations